Productivity, technology and efficiency of De Novo Islamic banks: empirical evidence from Malaysia - Sufian, Fadzlan (Palgrave McMillan, 2010)
The impact of foreign banks ’ entry on the conventional banking sector has been well documented in the literature. However, empirical evidence on the impact of foreign banks ’ entry on the Malaysian Islamic banking sector is completely missing from the literature. By employing the Malmquist Productivity Index method, the article provides, for the first time, empirical evidence on the impact of foreign banks ’ entry on the efficiency and productivity of the Islamic banking sector. The empirical findings indicate that the De Novo foreign Islamic banks have been relatively more efficient and productive compared to their domestic and foreign Islamic bank counterparts. The results also suggest that the Malaysian Islamic banking sector has exhibited a higher level of total factor productivity during the post De Novo foreign Islamic banks ’ entry period.